Thermal Analysis of Staggered Pin Fin Heat Sink for Central Processing Unit - Mohd Annuar, Khalil Azha; Mohd Ab Halim, Mohd Firdaus; Ismail, Fatimah Sham; Madiha , Zahari; Siti Halma, Johari; Harun, Mohamad Haniff (2015)
The advancement of microelectronics technology in producing high clock speed and power density’s central processor unit (CPU) indirectly related to thermal management issue. This is a major challenge to the manufacturers, designers and researchers to find the optimum design of the cooling system. If the problem is not being tackled, it will become a major setback to the development of electronic components and devices in the next five to ten years. The most popular technique used in the electronic devices is a metal heat sink with high heat transfer rate. The choice and suitable for the optimal heat sink design are needed in order to control and increase the heat dissipation. In this paper, 3D simulation staggered pin fin heat sink is designed and analyzed using COMSOL Multiphysics software. The finding of this study then is used to propose an optimal staggered pin fin arrangement of heat sink design that could give better thermal performance.